In vitro Propagation of Vanda testacea (Lindl.) Reichb. F, a Medicinally Important Threatened Orchid (Plant Tissue Culture and Biotechnology, 2022)
The present study was planned to enable in vitro conservation of Vanda testacea, a highly medicinal orchid species through in vitro asymbiotic seed germination technique in Mitra orchid medium supplemented with cytokinins (Kn - 4.65 μM, BAP - 4.44 μM), and auxin (NAA- 5.37 μM). The germination frequency and initiation of germination was higher in NAA augmented medium and seedlings developed in 12.50 ± 0.50 weeks. Coconut water (20%) proved optimum for the multiplication of protocorm like bodies. Activated charcoal successfully checked the release of brownish exudates in the cultures.Plant Tissue Cult. & Biotech. 31(2): 153-160, 2021 (December)